Diseño de un plan de importación de artículos tecnológicos, piezas y repuestos de celulares chinos al mercado colombiano (2021)
China has a wide variety in mass industrial production, including the technology products sector thanks to growth and innovation that is strengthened day after day, making China a very attractive economy to invest and import different cheaper products and manage to sell them at a higher price. This work aims to make a brief review of a marketing plan and study of financial viability in order to enter the market of technological articles according to the needs and preferences of the Bogotan consumer. In addition, this research work seeks to guide the import process, in accordance with the regulation and customs procedures that are presented at each stage of this activity, in the field of foreign trade.